Supervision and Accountability of Sakip Performance: Evidence from the Tasikmalaya City Government - Sundawa Bachtiar (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Public performance accountability has become a strategic requirement in modern governance, along with the increasing need for transparency and results-oriented governance. The Government Agency Performance Accountability System (SAKIP) was designed to ensure performance measurability, but its implementation at the regional level still faces substantial challenges. This study aims to analyze SAKIP performance oversight and accountability in the Tasikmalaya City Government using a strategic management approach. The theoretical study focuses on the concepts of public accountability, New Public Management, and strategic management. The research method employed a qualitative, descriptive-analytical approach through documentation studies, in-depth interviews, and observations, with interactive data analysis. The results indicate that SAKIP oversight is supported by adequate regulations and evaluation mechanisms, but it still tends to be administrative and does not fully meet the stated objectives. The discussion emphasizes the need for strengthening human resource capacity, consistent follow-up on recommendations, and integrating performance information systems so that SAKIP can function as a strategic instrument for improving local government performance